If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3x+2=12x+5
We move all terms to the left:
-3x+2-(12x+5)=0
We get rid of parentheses
-3x-12x-5+2=0
We add all the numbers together, and all the variables
-15x-3=0
We move all terms containing x to the left, all other terms to the right
-15x=3
x=3/-15
x=-1/5
| 15+n×4=63 | | -1=-1+p/9 | | 8-9p-10=-4p+23. | | -5+-1s=-10 | | -5.3m-13.73=19.01-1.2m-5.68 | | 2(x–2)+3=2x–1 | | -8x-15=2(7-4x)+8 | | 15+4×n=63 | | x(x-5)-5(x+5)=14 | | -b^2+3b-4=0 | | -4z=-21 | | r4=2.5 | | 4x+38=2 | | x2−6x+4=−7x+6 | | y+10=8y+24 | | -1+p/5=-3 | | 15.3k-7.77=-17.52+14.8k | | 37=8x | | 1-8/12=2a=5/3 | | -8(-1c)=-3 | | 2m^2-9m-5=6 | | -b+3b-4=0 | | s/6=1.8 | | 1x-3=54 | | 14+7n=14n+18 | | x3x8=x | | 58x-3=66 | | -6.21+3.8p=4.7p | | 0=8x-5/5x+4 | | -4+12p=284 | | -8x+18-2=-20-12x | | 2y-3(2y-3)=2-31 |